Effect of Educational Guidelines on Diabetic Patients' Knowledge, Attitude, and Self-Efficacy Regarding Use of Artificial Pancreas - Hayam Mohamed; Safaa El Sayed; Doaa Mahmoud (Evidence-Based Nursing Research)
Context: Artificial pancreas has a beneficial effect on controlling blood glucose levels. Nurses play a crucial role in helping diabetic patients through educational guidelines that increase their knowledge and improve their attitude and self-efficacy regarding the use of artificial pancreas as a new technology to help continuously control blood glucose levels.